2013
DOI: 10.1111/jpc.12206
|View full text |Cite
|
Sign up to set email alerts
|

Early developmental outcome following surgery for oesophageal atresia

Abstract: This study found a lower than expected developmental score for infants following surgery for OA/TOF in the expressive language subscale compared with the healthy control infants. These findings support concerns over the potential impact of OA/TOF and its effects on development. Further studies, including continuing developmental review to determine whether these differences persist and their functional importance, should be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…The scarce data on neurodevelopmental outcome in OA-patients are summarized for different age categories in Table 1 scores for non-syndromal OA-patients generally were within the normal ranges (20)(21)(22). In the study by Walker and co-workers, however, the mean score on language expression at one year was significantly below the norm (21).…”
Section: Neurodevelopmental Outcomementioning
confidence: 92%
“…The scarce data on neurodevelopmental outcome in OA-patients are summarized for different age categories in Table 1 scores for non-syndromal OA-patients generally were within the normal ranges (20)(21)(22). In the study by Walker and co-workers, however, the mean score on language expression at one year was significantly below the norm (21).…”
Section: Neurodevelopmental Outcomementioning
confidence: 92%
“…After screening of title/abstract followed by full text, 23 papers 6,7,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] reporting on 895 children met our inclusion and exclusion criteria and were selected for systematic review (Table 1). There was a wide range in follow-up duration and time of assessment from 12 months up to 60 months of age.…”
Section: Resultsmentioning
confidence: 99%
“…6,7,25,26,28,29,31,[36][37][38][39][40][41] This metaanalysis in 511 children resulted in a motor development score of 0.6 SD below the population average, indicated by the PDI score of 91 ± 14 (Fig 3A). One-sample t tests demonstrated that the mean PDI was significantly lower than the healthy population mean of 100 (P < .001; 95% CI 89.8-92.1).…”
Section: Meta-analysismentioning
confidence: 99%
See 2 more Smart Citations